(untitled) (Research, Society and Development, 2022)
The present research has the central theme in the proposal of active methodologies in Basic Education, from the use of digital resources as didactic instruments, taking as a target of practical application of the study a class of the third year of High School of the teaching institution Colégio Estadual Higino da Silveira, located in the city of Teresópolis/RJ. The objective of this research is to propose a didactic methodology that differs from traditional teaching practices, to promote more interaction between students and teachers, through the Mentimeter tool. To this end, its methodology is based on a bibliographic survey on topics that cover teaching and learning styles, as well as the insertion of technologies in education, followed by its juxtaposition to practical activities to carry out a final analysis considering the functionality and effectiveness of the proposed didactic strategy in producing better results in the teaching-learning process.